2018
DOI: 10.1177/0300985818766211
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Findings in Canine Pituitary Glands

Abstract: To optimize the histologic evaluation of hypophysectomy specimens, sections of 207 canine pituitary glands (196 postmortem, 11 hypophysectomy specimens) were reviewed. Adenohypophyseal proliferation was the most common (n = 79) lesion. Proliferative lesions were sparsely to densely granulated; the granules were usually basophilic to chromophobic and periodic acid-Schiff-positive. Adenohypophyseal proliferation was classified as hyperplasia (n = 40) if ≤2 mm diameter with intact reticulin network, as microadeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…4 This apparent difference in breed distribution could reflect differences in canine populations. The male:female ratio in the current case series was 3:1, but no reference population was available to determine whether this reflected a sex predilection for pituitary adenoma, which was not apparent in our retrospective study 16 and not reported in other studies.…”
contrasting
confidence: 54%
See 1 more Smart Citation
“…4 This apparent difference in breed distribution could reflect differences in canine populations. The male:female ratio in the current case series was 3:1, but no reference population was available to determine whether this reflected a sex predilection for pituitary adenoma, which was not apparent in our retrospective study 16 and not reported in other studies.…”
contrasting
confidence: 54%
“…At least 500 cells were counted (Count Tool in Adobe Photoshop CC 2015) in photographs taken at 400Â magnification. See the previous study 16 for details of the statistical analysis.…”
mentioning
confidence: 99%
“…Transsphenoidal surgical removal of functional pituitary tumors in dogs and cats can be performed by experienced surgeons with low morbidity and mortality 10–16 . Pituitary adenoma is the most common tumor of the pituitary fossa in dogs, but other sellar masses can occur, including meningioma, craniopharyngioma, ependymoma, germ cell tumors, and metastatic neoplasms 17–20 . NFSM become clinically significant when they cause compression of the hypothalamus and surrounding brain structures 10,18,21 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 , 14 , 15 , 16 Pituitary adenoma is the most common tumor of the pituitary fossa in dogs, but other sellar masses can occur, including meningioma, craniopharyngioma, ependymoma, germ cell tumors, and metastatic neoplasms. 17 , 18 , 19 , 20 NFSM become clinically significant when they cause compression of the hypothalamus and surrounding brain structures. 10 , 18 , 21 TSH is less commonly performed for NFSM producing clinical signs due to mass effect.…”
Section: Introductionmentioning
confidence: 99%
“…One study also described the surgical removal of an epidermoid cyst in the fourth ventricle via suboccipital craniotomy and partial first cervical laminectomy (16). Cell proliferations of the pituitary gland are common in dogs, and result in the formation of micro- or macroadenomas, adenocarcinomas, hyperplasia, craniopharyngeal duct cysts, secondary neoplasms, and hypophysitis (17). Functional disturbance of the pituitary gland, which causes canine hypercortisolism (central Cushing syndrome), is found in most cases (18, 19).…”
Section: Introductionmentioning
confidence: 99%